Research on the segments performance of the innovative startups ecosystem in the Russian Federation - B. E. Tokarev (Управление)
With the determination of the number of new innovative startups businesses, the situation is even more complicated, not only in our country, but also in most countries of the world. In the proposed work, the author made an attempt to implement one of the possible approaches to introducing transparency – an assessment of each of the segments of the startup-launches ecosystem separately. The paper gives the results of study on the evaluation the launch indicators of new startups in the Russian venture market. The article identifies the segments of the venture ecosystem that are directly involved in the launch of new startups. The study obtained an estimate of the number of startups, small and medium-sized companies as well as entrepreneurial startups. To characterize the number of new startups, the author introduces the term performance of segments of the ecosystem of innovative startups. This indicator allows you to use the quantitative characteristics of individual segments and compare them with each other. To obtain quantitative values of newly launched startups, the author conducted a selective telephone survey of representatives of these segments of the ecosystem and collected official data published on the Internet. The author carried out the processing of some data on the basis of the statistics of median values of the estimate of the number of new startups that started sales during 2019. The author collected data for 2020 from secondary sources. The study showed that 4,817 new startups with signs of innovation were launched in Russia in 2020, and an increase of 26 % compared to the previous year. The estimates obtained do not contradict with the published data on the state of the venture industry during the pandemic.